2004
DOI: 10.1023/b:ifla.0000033026.91221.ed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone Exposure on Intracellular Glutathione Redox State in Cultured Human Airway Epithelial Cells

Abstract: Intracellular oxidation and reduction (redox state) correspond closely to the surrounding environment. Most environmental factors affecting this balances such as oxidants, ultraviolet light, radioactive emissions, infections, and allergic reactions represent oxidative stress upon cells. We examined intracellular redox state after oxidative stress upon cultured human airway epithelial cells (Calu-3) by measuring reduced (GSH) or oxidized (GSSG) glutathione. We studied cytokine production, which is related to gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…At 6-12 h after A549 cells and NHBE cells were exposed to RSV, the intracellular redox state changed to a severely oxidized state, followed by a prolonged reduced state. Airway epithelial cells have an effective mechanism to improve an oxidized state, particularly the glutathione redox system, which can rapidly return cells from an oxidized to a reduced state [26]. Although previous studies have demonstrated an association between RSV infection and oxidative stress [31,32], this is the first study that documents the time-dependent effect of RSV infection on the intracellular redox state and proved that RSV induce oxidative stress in cultured human airway epithelial cells.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…At 6-12 h after A549 cells and NHBE cells were exposed to RSV, the intracellular redox state changed to a severely oxidized state, followed by a prolonged reduced state. Airway epithelial cells have an effective mechanism to improve an oxidized state, particularly the glutathione redox system, which can rapidly return cells from an oxidized to a reduced state [26]. Although previous studies have demonstrated an association between RSV infection and oxidative stress [31,32], this is the first study that documents the time-dependent effect of RSV infection on the intracellular redox state and proved that RSV induce oxidative stress in cultured human airway epithelial cells.…”
Section: Discussionmentioning
confidence: 76%
“…The current results suggest that RSV infection up-regulated IL-8 and other cytokine/chemokine production by means of oxidative stress in A549 cells and NHBE cells. In a previous study, oxidative stress affected the signal transfer system in airway epithelial cells resulting in up-regulation of cytokine/chemokine production, especially of IL-8 [26].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This result could be due to the sampling time point, since it has been shown to a reliable biomarker in nasal lavage fluid (Keman et al 1998;Sienra-Monge et al 2004). In the in vitro study of Todokoro et al (2004), it was observed that the IL-8 production started to increase after the second hour post-exposure, and only after 6 h did the upregulation of this cytokine become apparent. Therefore, we possibly missed this time point.…”
Section: Discussionmentioning
confidence: 99%